Mechanical thrombectomy versus medical care alone in large ischemic core: An up-to-date meta-analysis. Issue 1 (February 2022) - Jiang, Qianmei; Wang, Huaishun; Ge, Jian; Hou, Jie; Liu, Ming; Huang, Zhichao; Guo, Zhiliang; You, Shoujiang; Cao, Yongjun; Xiao, Guodong
Objective: We compared outcomes and adverse events of thrombectomy versus medical management in acute ischemic stroke (AIS) patients with baseline large infarct core. Methods: We searched Ovid MEDLINE(R) ALL, Cochrane Library Clinical Controlled Trials and EMBASE from inception to January 2021 for studies comparing thrombectomy and medical management alone in AIS patients who had ASPECTS <=7 or ischemic core volume >=50 ml. Imaging modalities to valuate ASPECTS and core volume were without restriction. The functional outcome was measured by mRS (modified Rankin Scale) score 0-2 at 90 days or discharge. The safety end point included the rates of mortality and sICH (symptomatic intracranial hemorrhage) or PH2 (parenchymal hematoma type 2). Results: Fourteen studies with a total of 2547 patients (thrombectomy n = [1197]; medical care alone [n = 1350]) fulfilled our criteria. As for patients with low ASPECTS, pooled results indicated a higher odds of good functional outcome (OR = 3.47; 95% CI 1.99 to 6.07; P < 0.0001, I 2 =66%) and a lower risk of mortality (OR = 0.62; 95% CI 0.46 to 0.83; P = 0.001, I 2 =32%) in thrombectomy group compared with no thrombectomy group, but the risk of sICH or PH2 did not differ between two groups. As for patients with large core volume, both functional outcome and safety end point between two groups showed no statistically significant difference. Conclusion: Thrombectomy remained safe and effective by careful selection in patients with low ASPECTS. More studies were warranted to explore contraindications for mechanical thrombectomy in AIS patients, especially in patients with large core volume.